2019
DOI: 10.1155/2019/4924306
|View full text |Cite
|
Sign up to set email alerts
|

Wave‐Based Method for Free Vibration Analysis of Orthotropic Cylindrical Shells with Arbitrary Boundary Conditions

Abstract: The wave-based method (WBM) is a feasible method which investigates the free vibration characteristics of orthotropic cylindrical shells under general boundary conditions. Based on Reissner–Naghid’s shell theory, the governing motion equation is established, and the displacement variables are transformed into wave functions formed to satisfy the governing equations. On the basis of the kinematic relationship between the force resultant and displacement vector, the overall matrix of the shell is established. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Submitting Eq. (27) into Eq. (25), the governing equation of the nanobeam related to the wave functions form in the matrix form can be obtained as: (27) w = We jkx e −j t = Θe jkx e −j t Φ = Γe jkx e −j t = Υe jkx e −j t…”
Section: Wave-based Methods For the Magneto-electro-thermo-elastic Nanmentioning
confidence: 99%
See 1 more Smart Citation
“…Submitting Eq. (27) into Eq. (25), the governing equation of the nanobeam related to the wave functions form in the matrix form can be obtained as: (27) w = We jkx e −j t = Θe jkx e −j t Φ = Γe jkx e −j t = Υe jkx e −j t…”
Section: Wave-based Methods For the Magneto-electro-thermo-elastic Nanmentioning
confidence: 99%
“…He et al [20] proposed WBM in the free vibration characteristics of cross-ply composite laminated cylindrical shell with arbitrary boundary conditions. At the same time, wavebased method is used to study the vibration characteristics of many engineering application structures, such as cylindrical shell structures [21][22][23], submerged ring-stiffened conical shells [24], elastic coupling structure of cylindrical shell and annular plate [25], rotating shell with ring stiffener in T cross section [26] and some composite laminated structures [27][28][29]. From the above literature analysis, it can be shown that there is no related reference to analyze the wave propagation characteristics of magneto-electro-thermo-elastic nanobeam by WBM.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, with the development of Aerospace Engineering, the finite element method gradually formed a complete system. Besides, because the matrix displacement method is the elementary form of the finite element method [5][6][7][8]. The matrix displacement method is also called the member finite element method.…”
Section: Introductionmentioning
confidence: 99%